Differences in Triage Thresholds for Patients Presenting with Possible Acute Coronary Syndromes: More than Meets the Eye. (1st March 2006) - Milch, Catherine E.; Kent, David M.; Ruthazer, Robin; Pope, Hector J.; Aufderheide, Thomas P.; McNutt, Robert A.; Selker, Harry P.
Abstract : Background: Many studies have shown differences in cardiac care by racial/ethnic groups without accounting for institutional factors at the location of care. Objective: Exploratory analysis of the effect of hospital funding status (public vs private) on emergency department (ED) triage decision making for patients with symptoms suggestive of acute coronary syndromes (ACSs) and on the likelihood of ED discharge for patients with confirmed ACS. Study Design and Setting: Secondary analysis of data from a randomized controlled trial of 10, 659 ED patients with possible ACS in five urban academic public and five private hospitals. The main outcome measures were the sensitivity and specificity of hospital admission for the presence of ACS at public and private hospitals and the adjusted odds of a patient with ACS not being hospitalized at public versus private hospitals. Results: Of 10, 659 ED patients, 1, 856 had confirmed ACS. For patients with suspected ACS, triage decisions at private hospitals were considerably more sensitive (99 vs 96%; p < .001) but less specific (30 vs 48%; p < .001) than at public hospitals. The difference between hospital types persisted after adjustment for multiple patient-level and hospital-level characteristics. Conclusion: Significant differences in triage for patients with suspected ACS exist between public and private hospital EDs, even after adjustment for multiple patient demographic, clinical, and institutional factors. Further studies are needed to clarify the causes of the differences.